The association between life events and mental health among adults in Java, Indonesia: Investigating the moderating effects by education, asset index, and rural-urban area of residence - Sri Idaiani; Mashita Fajri; Irmansyah Irmansyah; Jonathan Gibson; Jack Wilkinson; Herni Susanti; Helen Brooks; Penny Bee; Asri Maharani (PLoS ONE, 2026)
Life events (LE) are significant experiences (e.g., bereavement, illness, or job loss) that require psychological adjustment and may contribute to mental health disorders like depression and anxiety. Indonesia faces a rising burden of these conditions, yet limited research has explored their relationship with LE in its diverse socio-cultural context. This study examines the associations between LE, depression, and anxiety among adults in Java, Indonesia. It further explores how these associations vary by education, asset ownership (proxy of household wealth) index, and rural-urban area of residence. We used cross-sectional data from the baseline of the Sustainable Treatment and Care for Anxiety and Depression (STAND) 2023 longitudinal household survey. The study included 19,186 participants aged 18 years and older. Depression and anxiety were assessed using the CES-D-10 and GAD-7 scales, respectively, both validated for this population. LE was measured using the Social Readjustment Rating Scale, which categorises exposure into low, moderate, and high-stress levels over the past 12 months. Logistic regression was used to evaluate the associations, adjusting for demographic, socioeconomic, lifestyle, and health-related factors. Both primary models (main effects only) and interaction models (to explore moderation) were fitted. Overall, 4.4% of respondents reported depressive symptoms, and 8.5% reported anxiety. In the primary models, experiencing moderate or high levels of LE was significantly associated with depression (AOR = 3.1, 95% CI: 2.6–3.6; AOR = 10.2, 95% CI: 8.0–12.9, respectively) and anxiety (AOR = 2.7, 95% CI: 2.5–3.1; AOR = 6.5, 95% CI: 5.3–8.0, respectively). These associations were moderated by socioeconomic factors. Higher education, a higher asset index, and urban residence were associated with lower odds of anxiety and depression. Interventions should prioritise mental health literacy and access to care, particularly in rural and socioeconomically disadvantaged populations.